Evaluation of Hemodynamic and Blood Oxygen Metabolism Alterations in Parkinson's Disease Using Quantitative MRI - Lv, Xinyi; Ye, Rong; Wen, Jie; Xie, Qiang; Chen, Yuhua; Hu, Panpan; Wang, Kai (Current Neuropharmacology, 2025)
<span class=
Keywords: deoxygenated cerebral blood volume